2013
DOI: 10.1002/dac.2645
|View full text |Cite
|
Sign up to set email alerts
|

High‐capacity soliton transmission for indoor and outdoor communications using integrated ring resonators

Abstract: SUMMARYA system consisting of a series of microring resonators, incorporating an add/drop system, is presented in order to create ultra‐short spatial and temporal single and multisoliton pulses, which can be used for indoor and outdoor optical communications. Chaotic noise can be generated by a bright soliton pulse propagating inside a nonlinear microring resonator system. The results obtained show that a single temporal and spatial soliton pulse, with full width at half maximums of 75 fs, 80 fs, 700 fs, 4.4 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Chaotic signals have some properties such as broadband, orthogonality and complexity aspects, which prompt researches in the areas of nonlinear science, communication technology and signal processing [64][65][66][67]. The concern in chaotic communications was due to the foreseen good properties of the chaotic signals in the fields of security systems or broadband multiple access systems.…”
Section: Ring Resonatorsmentioning
confidence: 99%
“…Chaotic signals have some properties such as broadband, orthogonality and complexity aspects, which prompt researches in the areas of nonlinear science, communication technology and signal processing [64][65][66][67]. The concern in chaotic communications was due to the foreseen good properties of the chaotic signals in the fields of security systems or broadband multiple access systems.…”
Section: Ring Resonatorsmentioning
confidence: 99%
“…[20][21][22] The long distance communication can be performed by using high optical output of the soliton signals within the ring resonator system. [23][24][25] A soliton band can be generated by using a Gaussian pulse propagating within a ring resonator system. [26][27][28] We use a system of MRRs connecting to a panda ring resonator to generate a high frequency band of optical soliton pulses.…”
Section: Introductionmentioning
confidence: 99%
“…One new feature of this specific type of ring resonator, which introduces a system of nanoscale-sensing transducers based on the add/drop ring resonator was presented by Amiri et al [10,11]. They have shown that the multisoliton can be generated and controlled within a modified add/drop ring resonator [12,13].…”
Section: Introductionmentioning
confidence: 99%